Long-term exposure to air pollution and stroke incidence: A Danish Nurse cohort study. (September 2020) - Amini, Heresh; Dehlendorff, Christian; Lim, Youn-Hee; Mehta, Amar; Jørgensen, Jeanette T.; Mortensen, Laust H.; Westendorp, Rudi; Hoffmann, Barbara; Loft, Steffen; Cole-Hunter, Tom; Bräuner, Elvira V.; Ketzel, Matthias; et al.
Abstract: Ambient air pollution has been linked to stroke, but few studies have examined in detail stroke subtypes and confounding by road traffic noise, which was recently associated with stroke. Here we examined the association between long-term exposure to air pollution and incidence of stroke (overall, ischemic, hemorrhagic), adjusting for road traffic noise. In a nationwide Danish Nurse Cohort consisting of 23, 423 nurses, recruited in 1993 or 1999, we identified 1, 078 incident cases of stroke (944 ischemic and 134 hemorrhagic) up to December 31, 2014, defined as first-ever hospital contact. The full residential address histories since 1970 were obtained for each participant and the annual means of air pollutants (particulate matter with diameter < 2.5 µm and < 10 µm (PM2.5 and PM10 ), nitrogen dioxide (NO2 ), nitrogen oxides (NOx)) and road traffic noise were determined using validated models. Time-varying Cox regression models were used to estimate hazard ratios (HR) (95% confidence intervals (CI)) for the associations of one-, three, and 23-year running mean of air pollutants with stroke adjusting for potential confounders and noise. In fully adjusted models, the HRs (95% CI) per interquartile range increase in one-year running mean of PM2.5 and overall, ischemic, and hemorrhagic stroke were 1.12 (1.01–1.25), 1.13 (1.01–1.26), and 1.07 (0.80–1.44), respectively, and remained unchanged after adjustment for noise. Long-term exposure to ambient PM2.5 was associated with the risk of stroke independent of road traffic noise.